Pulmonary interstitial glycogenosis: Diagnostic evaluation and clinical course. Issue 12 (18th July 2018) - Liptzin, Deborah R.; Baker, Christopher D.; Darst, Jeffrey R.; Weinman, Jason P.; Dishop, Megan K.; Galambos, Csaba; Brinton, John T.; Deterding, Robin R.
Abstract: Objectives: We sought to describe the phenotype for patients with P.I.G. including presentation, evaluation, cardiac co‐morbidities, high resolution computed tomography findings, and outcomes. Methods: With institutional review board approval, we performed a retrospective review of patients with biopsy‐proven P.I.G. Biopsies, high resolution chest computed tomography, and cardiac evaluations were reviewed and characterized by experts in each field. Results: Sixty‐two percent of the patients were male. The median gestational age was 37 weeks (range 27‐40). The median age at biopsy was 1.6 months (range 0.3‐6 months). Structural heart disease was present in 63% of patients. Pulmonary hypertension (diagnosed by echocardiogram and/or cardiac catheterization) was noted in 38% of patients. Alveolar simplification was present in 79% of patients. Fifty percent of available biopsies revealed patchy disease. An increase in age at biopsy was associated with patchy (vs diffuse) disease. Ninety‐two percent of patients were treated with systemic corticosteroids. Median age at last follow‐up was 1234 days with a range of 37 days to 15 years. At the time of last follow‐up, 12 patients were off all support, eight were on supplemental oxygen, two were mechanically ventilated, one underwent lung transplantation, and one died. CT findings commonly included ground glass opacities (86%) and cystic change (50%). Conclusions: The P.I.G. phenotype has not been comprehensively described, and poor recognition and misconceptions about P.I.G. persist. P.I.G. is a disease that presents in early infancy, requires significant medical intervention, and frequently is seen in association with alveolar simplification and/or cardiovascular disease. CT findings include ground glass opacities and cysts. Patients should be monitored for pulmonary hypertension. Without life‐threatening comorbidities, many patients do well over time, although respiratory symptoms may persist into adolescence.